How to Enter Article Scientific Journals into SINTA-Index - Harisa Mardiana; Trida Trida; Yopie Chandra (Universitas Lambung Mangkurat, 2023)
The purpose of this community service is to provide convenience to journal managers, researchers, and lecturers in publishing scientific journals at SINTA. In addition, the publication of scientific journals on the SINTA - Index positively impacts the journals it manages and provides convenience for online readers. This seminar was organized by the new journal Religious Policy (REPO) from the Center for Training and Development (Puslitbang) of the Ministry of Religion, Jakarta. This seminar uses three stages of the community service method: (1) the agenda for cooperation, after obtaining sources and determining the subject matter and arranging event activities; (2) implementation of activities in the form of lectures, discussions, and questions and answers on the socialization of the SINTA-Index journal; (3) evaluation of activities by returning questionnaires from 32 seminar participants. The results of this seminar were that all participants and journal managers understood how to enter scientific journal articles so that their journals could be in SINTA-indexed. The implication is that all participants want scientific journal articles indexed by SINTA, and journal managers want their journals to be SINTA accredited.